VACCINE HESITANCY OF PARENTS AND FAMILY MEMBERS OF CHILDREN AND THE CONTROL OF IMMUNOPREVENTABLE DISEASES - Viana, Izabella da Silva; Cursino, Emília Gallindo; Miranda, Priscila da Silva; Silva, Liliane Faria da; Machado, Maria Estela Diniz (Cogitare Enfermagem, 2023)
Objective: to analyze, in scientific productions, the reasons that lead parents and family members of children to vaccine hesitancy in the context of control of immunopreventable diseases. Method: integrative review using the following informational resources: Scientific Electronic Library Online, Latin American and Caribbean Literature on Health Sciences, Nursing Database, Índice Bibliográfico Español en Ciencias de la Salud, Medical Literature Analysis and Retrieval System Online, and Cumulative Index to Nursing and Allied Health Literature. A time cut-off from 2016 to 2021 was used. Results: Twenty-four articles comprised the final sample, and two categories emerged: Un(knowledge) about vaccines; and In(decision) and lifestyle. Conclusion: this study contributes to professional practice, encouraging health units' managements to establish strategies for interventions with the hesitant. Vaccine refusal or delay in vaccination should be considered by these professionals a window of opportunity to approach parents and family members.